PROBLEM RESEARCH IN SECOND LANGUAGE ACQUISITION - Saydaliyeva, Dilfuza (Журнал иностранных языков и лингвистики, 2023)
Our article presents the results of a corpus-based study on language interventions, which are mainly used in speech-psychological language interventions. The analysis focuses on the norms of one language under the influence of another language, observed in the speech of people who speak those languages. Analyzed examples include interventions in phonology, morphology, syntax, lexicon, and word formation.